The Tin Mining Conflict (An Analysis of Interest Group’s Access and Policy Innovation to The Use of Natural Resources In The Water of Teluk Kelabat Dalam, Belinyu District) - Murni Zaina Murni; Ibrahim Ibrahim; Bahjatul Murtasidin (International Journal of Regional Innovation, 2022)
This study discusses the access to the use of natural resources in the waters of Teluk Kelabat Dalam, Belinyu which is an area that has considerable potential natural resources. Regional Regulation of the Bangka Belitung Islands Province Number 3 of 2020 concerning RZWP3K states that the area is included in the capture fisheries zone, port zone, and tourism zone. Precisely in Article 29 letter a, the Teluk Kelabat Dalam Belinyu Bangka Regency is the developing zone area of the capture fisheries, hereinafter referred to as KPU-PT. However, in this area, it appears that there are tin mining activities carried out by KIP PT Timah and community mining where the legality of those is not clear and the amount is not appropriate, which triggers conflict or rejection from the fishing community. The purpose of this study is to analyze the interest group’s access to the use of natural resources in the waters of Teluk Kelabat Dalam, Belinyu. The theory used in this study namely the Access theory of Jesse Ribot and Nancy Lee Peluso. The method used in this study is a qualitative research method. While the data collection techniques in this study are interviews, observation, and documentation. The result of this study is that the interest group in the utilization of natural resources in the waters of Teluk Kelabat Dalam, Belinyu include the fishermen, tin miners, the government, and tin companies. First, regarding the right-based access mechanism, fishermen have the legal rights in accordance with Regional Regulation Number 3 of 2020 concerning RZWP3K which is stated as a capture fisheries zone. Whereas, it is illegal for tin miners owned by the community since the legality has not been clear. In addition, the government’s right is legal in accordance with formal regulation. The access of tin company is legal through IUP ownership with Regent’s Decree Number 188.45/465/TAMBEN/2010. Second, the structural and relational-based access mechanisms of these actors are influenced by several factors such as capital factors, social identity, authority, technology, social relations, and so on and so forth that are able to determine the benefits or power and reciprocal network relationships between them.